Change in drivers of mangrove crown displacement along a salinity stress gradient. (23rd October 2018) - Vovides, Alejandra G.; Berger, Uta; Grueters, Uwe; Guevara, Roger; Pommerening, Arne; Lara‐Domínguez, Ana Laura; López‐Portillo, Jorge
Abstract: Crown displacement in trees is an adaptive response driven by neighbours that optimizes space use and reduces competition. But it can also be the result of wind force. Although morphological responses to neighbours have been well studied, the interplay between neighbours and wind in driving crown shape, and the implications for plant interactions remain poorly understood. However, it is crucial to predict such changes in vegetation structure and function under the scope of global change. We test the hypothesis that aboveground interactions are reduced with increasing soil stress and that wind becomes the main driver of crown shape in mangrove forests. We investigated the effect of neighbours and wind intensity and direction on crown displacement of mangrove canopy and below canopy trees along a salinity gradient, and assessed crown asymmetry for three mangrove tree species, as well as the contribution of crown displacement on reducing crown‐projected area overlap and thus neighbourhood competition. Results show that crown displacement of canopy trees is strongly influenced by winds at all salinities. At low salinities, competition for space accounted for 48% of crown displacement away from neighbours, compared to 49% found for the synthetized effects of wind and neighbours. While trees below the canopy displace their crowns away from their neighbours, no response to wind could be detected. This can be due to the wind protection conferred by a dense canopy stand related to bigger crowns that effectively reduce wind drag. At higher salinities, there was a reduction in canopy overlap due to crown displacement, which suggests reduced aboveground plant interactions with increasing soil stress. While neighbourhood avoidance is a fundamental strategy for optimal light foraging, this study shows that wind strength and directionality are main drivers of crown shape with increasing stress and highlights their potential influence in plant interactions and forest structure, pointing to an increased susceptibility of trees to disturbances that should be further studied. Aplain language summary is available for this article. Abstract : Plain Language Summary